ESTETIKA DAN ETIKA DALAM DONGENG ANAK ISLAMI - Septiaji, Aji; Kusmana, Suherli; Syarifah, Eva Fitriani (Indonesian Journal of Islamic Studies (IJIS), 2025)
This study aims to examine the integration of aesthetic and ethical elements in Islamic children's stories as part of children's literature that promotes Islamic religious values. Islamic children's stories serve not only as a medium of entertainment but also as a means of instilling character and spirituality from an early age. This study uses a qualitative descriptive approach with content analysis of selected stories texts, namely 9 out of 30 Dongeng Sebelum Tidur untuk Anak Muslim (Bedtime Stories for Muslim Children) by Kidh Hidayat and MB. Rahimsyah. The analysis focuses on aesthetic aspects such as narrative structure and style of language as well as Islamic ethical aspects such as moral values of honesty, empathy, and responsibility. The results of the study indicate that the stories present an aesthetically pleasing narrative with communicative language, effectively capturing children's attention while facilitating understanding of the moral messages. Islamic ethical values are implicitly embedded in the plot and characters, making them an effective medium for character education. This study recommends the utilization of Islamic stories as religious literacy materials to support values-based learning in elementary schools.